Impact of Zinc Fertilization on Potato (Solanum tuberosum L.) Yield, Zinc Use Efficiency, Quality and Economics in Entisol of West Bengal - Krishnendu Ray, Lalita Rana; Kaushik Majumdar, Hirak Banerjee, Sukamal Sarkar, Prahlad Deb, Sudarshan Kumar Dutta (Journal of the Indian Society of Soil Science, 2016)
The present investigation was carried out during winter seasons of 2013-14 and 2014-15 to assess the zinc (Zn) requirements of potato on a new alluvial soil (Entisol) of West Bengal. Potato received varying levels of Zn as soil application (0, 1.5, 3.0, 4.5 and 6.0 kg Zn ha-1). While no impact of Zn fertilization was observed on the germination percentage, leaf area index (LAI), and haulm dry weight, it significantly improved the tuber and total dry weight (sum of haulm and tuber weight) over control, though the Zn levels were statistically at par. The total tuber yield was significantly influenced with the increase in the levels of Zn and the highest tuber yield (28.7 t ha-1) with 4.5 kg Zn ha-1. The Zn rate of 1.5 kg ha-1 and beyond increased Zn uptake by potato (tuber, haulm and total). While agronomic efficiency (AEZn) and physiological efficiency (PEZn) showed no effect of Zn fertilization, the recovery efficiency (REZn) decreased significantly with the increase in Zn level from 1.5 to 4.5 kg Zn ha-1. Total soluble solids (TSS), total acidity and ascorbic acid content of potato tuber remained unaffected by Zn fertilization, but total starch content (dry weight basis) of tuber increased with the increasing Zn doses, thus potato fertilized with 6.0 kg Zn ha-1 recorded the highest starch content (58.05 mg 100 g-1). Net return from Zn application and benefit: cost ratio were highest at application rate of 4.5 kg Zn ha-1.